2019
DOI: 10.1103/physreva.99.052117
|View full text |Cite
|
Sign up to set email alerts
|

Quantum walker as a probe for its coin parameter

Abstract: In discrete-time quantum walk (DTQW) the walker's coin space entangles with the position space after the very first step of the evolution. This phenomenon may be exploited to obtain the value of the coin parameter θ by performing measurements on the sole position space of the walker. In this paper, we evaluate the ultimate quantum limits to precision for this class of estimation protocols, and use this result to assess measurement schemes having limited access to the position space of the walker in one dimensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…The minimum value of the F θ is compatible with the results in Ref. [43], where numerical evaluation for each initial state of the coin was required. 47) for θ = π/4 as a function of time when a maximizing (ry = 0, solid red line) or a minimizing (eigenstates of σy, dashed blue line) initial state is selected.…”
Section: Single-parameter Quantum Metrologysupporting
confidence: 83%
See 2 more Smart Citations
“…The minimum value of the F θ is compatible with the results in Ref. [43], where numerical evaluation for each initial state of the coin was required. 47) for θ = π/4 as a function of time when a maximizing (ry = 0, solid red line) or a minimizing (eigenstates of σy, dashed blue line) initial state is selected.…”
Section: Single-parameter Quantum Metrologysupporting
confidence: 83%
“…This time, however, the initial state of the coin is parametrized by γ. The elements of the QFIm of the full space can be derived by means of (41)(42)(43) and are…”
Section: Two-parameter Quantum Metrology With Special Initial States ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that it is indeed possible to estimate the coin parameter of a DTQW with a singleparameter coin. However, the approaches that rely on QFI to predict the parameters in a DTQW share a similar constraint, viz, even though H w (θ) is a continuous, single-valued function over θ, the variations in the plot are small, and thus contribute to the error in determining θ [57]. In this work, we train various machine learning models and demonstrate that such models can indeed estimate the quantum walk parameters to a good accuracy.…”
Section: Introductionmentioning
confidence: 95%
“…It is known that the Quantum Fisher Information (QFI) [52][53][54][55] H w (θ) of a quantum walker's position quantifies a bound to the amount of information that can be extracted from the probability distribution [56,57]. It has also been shown that it is indeed possible to estimate the coin parameter of a DTQW with a singleparameter coin.…”
Section: Introductionmentioning
confidence: 99%